Refresh Pengetahuan Kader Posyandu Mengenai Pengukuran Antropometri Anak Di Wilayah Kerja Puskesmas Samarinda Kota - Reny Noviasty; Diny Qoyyimah (Jurnal Nasional Pengabdian Masyarakat, 2022)
Refreshing cadres' knowledge of anthropometric measurement procedures that are in accordance with standards is very important to be able to determine the proper nutritional status of children, especially for early detection and prevention of stunting. For this reason, it is important to increase knowledge through media of posters and leaflets that can be used by cadres at any time. Community service was carried out by involving 17 posyandu cadres in the working area of the Samarinda Kota health center in December 2022. The programs consisted of media design, followed by socialization and education at the posyandu. The media that has been designed is given to cadres during socialization and education. In addition, the practice of using media correction of anthropometric measurement procedures is also carried out. After being given education, there was an increase in pre-post test knowledge by 35.3%. It is necessary to periodically update the material of anthropometric measurement procedures to ensure the accuracy of measurements and measurement skills to evaluate the accuracy of cadre measurements.